Analysis of Weaknesses in Hybrid Learning : A Case Study on Ilmu Kealamiahan Dasar (IKD) Courses - Muhammad Syazali; Nova Fitriani Wahdah (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2024)
This study analyzed the weaknesses of hybrid learning implemented in IKD courses. This qualitative descriptive research was conducted within the Elementary School Teacher Education Program (PGSD) during preparation, planning, instruction, and learning outcomes assessment. Qualitative data were collected using observation and documentation methods. The collected data were analyzed using qualitative analysis techniques as proposed by Miles and Huberman. The weaknesses of hybrid learning identified in this study include coordination with senior lecturers whose expertise is not in science education, delays in submitting the SIMAKSI to the BKSDA, and limited CPMK to the science process skills (SPS). These objectives only encompass basic SPS, the absence of guidelines for report preparation, science topics restricted to ecosystems, multitasking challenges, a learning interval of only two weeks, assessment instruments relying solely on tests, and the implementation of tests conducted online. The findings of this study are expected to serve as evaluative material aimed at improving the implementation of hybrid learning in science courses, particularly in the context of IKD.